Brand Image Trust Digital Marketing Drive Nivea Men Purchasing Decisions: Citra Merek Kepercayaan Pemasaran Digital Mendorong Keputusan Pembelian Nivea Men - Mazin Daffa; Lintang Pratama Putra Andika; Dhea Wulan Arianti; Reza Dwi Juniar; Sigit Hermawan (Proceedings of The ICECRS, 2024)
General Background Technological advancements significantly alter contemporary consumer behavior by facilitating seamless access to online product information. Specific Background The male facial care market is experiencing intense competition, prompting companies to utilize online media for broader consumer reach and heightened credibility. Knowledge Gap While online strategies are prevalent, the exact mediating role of virtual platforms in translating corporate perceptions and consumer confidence into actual sales remains underexplored within specific male grooming segments. Aims This study analyzes the direct relationship of corporate perception and consumer confidence on buying choices, alongside examining online promotion as an intervening variable for male grooming products. Results Path analysis of 52 respondents revealed that corporate perception and consumer confidence directly dictate buying choices. Furthermore, corporate perception significantly shapes online promotional interactions, whereas consumer confidence does not. However, both corporate perception and consumer confidence successfully drive final transactions through online promotional mediation. Novelty The research delineates the distinct pathways where online platforms successfully mediate both corporate perception and consumer confidence, despite the latter failing to directly alter the online promotional variable itself. Implications Grooming companies should prioritize integrating strong corporate reputations with interactive online campaigns to secure competitive advantages and accelerate consumer acquisition. Highlights:• Reputation alongside consumer confidence directly shapes buying choices regarding male facial care items. • Online platforms successfully mediate relationships connecting corporate perception with final transactions. • Consumer certainty fails to directly alter online promotional interactions despite mediating sales. Keywords: Brand Image, Consumer Trust, Digital Marketing, Purchasing Decision, Facial Care